Cultural anchoring of women`s football or deception? Comparative historical analysis of the processes of institutionalization of the practice - Gozillon, A.; Bréhon, J. (Soccer & Society, 2024)
"More than a sporting event, the 2019 FIFA Women`s World Cup has been a cultural phenomenon (…) women`s football is attractive everywhere". If the words of the FIFA President reflect the institutional desire to promote the momentum generated by the French World Cup, a simple look at the rates of feminization is enough to highlight profound federal differences: 7.4% in France; 15.5% in Germany; 24.6% in England; 29.7% in Norway; 38.4% in Sweden; 55% in the USA. To explain such heterogeneity, recourse to socio-history and comparison can be valuable. By comparing six figures considered as exemplary, we highlight the distinctive and complementary impact of historical levers and brakes on the development of the practice: sporting (mega)events, the media, egalitarian public policies and federal sports policies thus seem to be decisive in describing, explaining and understanding, according to the periods selected, the processes of institutionalization and the observed cultural anchoring of so-called women`s football.